Multiscale stochastic computational homogenization of the thermomechanical properties of woven Cf/SiCm composites. (15th November 2019) - Choi, Ho-Il; Zhu, Fei-Yan; Lim, Hyungjun; Yun, Gun Jin
Abstract: This paper demonstrates a set of two-scale asymptotic computational homogenization formalisms of Cf /SiCm thermomechanical properties and proposes a 3D micro-to-mesoscale stochastic bridging methodology considering the uncertainties of the constituents' properties and geometries. For multiscale thermomechanical analyses, the thermal conductivity (TC), the coefficient of thermal expansion (CTE) and the elastic stiffness (ES) properties are homogenized at the microscale within the fiber tow. The proposed consistent multiscale bridging method models spatial random fields using the three-dimensional Karhunen-Loève (KL) expansion method with integration with a 3D FE-based computational homogenization model. We compare effects of two different uncertainties (i.e., geometric and spatial material randomness) to statistical variations of the effective thermomechanical properties at the microscale. By comparing with threshold COV values, we determine the thermomechanical properties to be modeled as random fields. At the mesoscale RVEs, we randomize the key twelve thermomechanical properties, perform two-scale computational homogenization and draw statistical variations at the mesoscale.